2019
DOI: 10.1128/jvi.01916-18
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of Avian and Seasonal Influenza A Viruses by a Virus-Specific Dicer-Substrate Small Interfering RNA Swarm in Human Monocyte-Derived Macrophages and Dendritic Cells

Abstract: Influenza A viruses (IAVs) are viral pathogens that cause epidemics and occasional pandemics of significant mortality. The generation of efficacious vaccines and antiviral drugs remains a challenge due to the rapid appearance of new influenza virus types and antigenic variants. Consequently, novel strategies for the prevention and treatment of IAV infections are needed, given the limitations of the presently available antivirals. Here, we used enzymatically produced IAV-specific double-stranded RNA (dsRNA) mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Instead of chemical synthesis and post-synthesis hybridization of RNA oligonucleotides, we produce high-quality molecules for RNAi using viral RNA polymerases and recombinant Giardia Dicer enzyme ( Levanova and Poranen, 2018 ). This results in a swarm of 25-bp-long Dicer-substrate siRNAs (DsiRNAs) ( Macrae et al, 2006 ; Romanovskaya et al, 2012 ), which can cover several kbp sequence of the target ( Nygardas et al, 2009 ; Niehl et al, 2018 ; Jiang et al, 2019 ). When introduced into a cell, such siRNAs are processed by the endogenous Dicer, which enhances the RNAi potency and efficacy ( Kim et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of chemical synthesis and post-synthesis hybridization of RNA oligonucleotides, we produce high-quality molecules for RNAi using viral RNA polymerases and recombinant Giardia Dicer enzyme ( Levanova and Poranen, 2018 ). This results in a swarm of 25-bp-long Dicer-substrate siRNAs (DsiRNAs) ( Macrae et al, 2006 ; Romanovskaya et al, 2012 ), which can cover several kbp sequence of the target ( Nygardas et al, 2009 ; Niehl et al, 2018 ; Jiang et al, 2019 ). When introduced into a cell, such siRNAs are processed by the endogenous Dicer, which enhances the RNAi potency and efficacy ( Kim et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The siRNA swarm contains predominantly 5′-monophosphates as only the single siRNAs originating from the very ends of the produced dsRNA molecules contain the 5′-triphosphate moiety, which could induce innate immunity responses. The swarm, comprising of numerous different siRNAs against the target, also widens the antiviral spectrum ( Paavilainen et al, 2016 ; Jiang et al, 2019 ) and minimizes the potential of emergence of viral variants resistant to a single siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our recent research [42] showed that an in vitro synthesized influenza A virus-specific siRNA efficiently inhibits the replication of several influenza A virus strains in human primary cells ( Fig. 3), confirming that a swarm of virus-specific siRNA can act as a broad-spectrum inhibitor.…”
Section: In Vitro Production Methods For Rna Moleculesmentioning
confidence: 59%
“…Designed target DNA sequences can be used to directly generate desired dsRNAs in a single-tube process combining T7 DdRp catalyzed ssRNA transcription and phi6 RdRp-based dsRNA synthesis. DsRNAs can then be further digested by Giardia intestinalis or human Dicer enzymes to generate the swarms of Dicer-substrate siRNA (DsiRNA) [39,42], followed by purification through anion-exchange chromatography on a monolithic QA column [38,39] or GEN-PAK FAX column (Supplementary Material and [36]) and NAP column desalting [38,39]. DsiRNA swarms generated in vitro can target multiple viral genomic sequences and mRNAs so that infection of viruses even with high genetic variation (e.g.…”
Section: In Vitro Production Methods For Rna Moleculesmentioning
confidence: 99%
See 1 more Smart Citation